UNSUR-UNSUR MITOS, ANIMISME, RITUS, DAN MAGI DALAM RITUAL PEMUJAAN DEWI SRI - Ananda, I Nyoman (PANGKAJA, 2012)
ABSTRACTThe worship of Dewi Sri is performed by Balinese people whose mostly occupation as farmers. This agricultural ritual aims at having their land fertilized. This article examining the practice of The worship of Dewi Sri ritual, including mythological motivation and trace of the local religion. The worhip of Dewi Sri verily worshipping Ida Sang Hyang Widhi, The Almighty God in His manifestation as the Goddes of fertilizer and prosperity. This ritual is close related to the local religion with magical and animism traces and stay still from modern change. Key Words: Dewi Sri, local religion, agriculture.